2019
DOI: 10.18061/emr.v13i1-2.6118
|View full text |Cite
|
Sign up to set email alerts
|

Listening to Improvisation

Abstract: Is there something peculiar in our appreciation of improvised music? How does knowing that the music we are listening to is improvised affect our experience? As a first step in answering these questions, I have conducted an experiment in which an audio recording of the very same piece of music – a saxophone/clarinet freely improvised duet – was presented to 16 listeners, either as an improvisation ("IMPRO" condition), or as the live performance of a composition for saxophone and clarinet ("COMPO" condition). L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 12 publications
0
9
0
1
Order By: Relevance
“…As such, individual roles and creative contributions to the overall output are constantly shifting and renegotiated over the course of the performance, and the creativity of the performance crucially depends on the way improvisers dynamically relate to one another. Interpersonal relations are thus at the very core of the practice of CFI (Clarke, 2005), the musicians’ dialogical engagements with one another acting as one of the primary locus of CFI’s aesthetic distinctiveness (Canonne, 2018a).…”
mentioning
confidence: 99%
“…As such, individual roles and creative contributions to the overall output are constantly shifting and renegotiated over the course of the performance, and the creativity of the performance crucially depends on the way improvisers dynamically relate to one another. Interpersonal relations are thus at the very core of the practice of CFI (Clarke, 2005), the musicians’ dialogical engagements with one another acting as one of the primary locus of CFI’s aesthetic distinctiveness (Canonne, 2018a).…”
mentioning
confidence: 99%
“…We will not address this debate here. However, Canonne (2018) demonstrated how these conceptions of structure are much more implied when a piece is described as a composition than when it is addressed as an improvisation, even when dealing with new music. It is shown that listeners tend to search for cues -structurally -when listening to a composition, given that a previous work by the composer is assumed.…”
Section: Form Structure and Perception Of Improvisationsmentioning
confidence: 99%
“…As such, we aim to investigate the following research question: are there differences in the perception of a possible structure when the given context is different? This question is raised due to recent experiments, such as the aforementioned study by Canonne and Garnier (2015), where the sequential form was put to test, and also from Canonne's (2018) experiment on the qualitative differences in listening to a musical piece defined as an improvisation or as a composition. Results from the latter show that participants tended to have a negative evaluation-in example, in terms of musical coherence and the overall structure of the piece-of pieces that were in reality free improvisations but were contextualized as compositions.…”
mentioning
confidence: 99%
“…Others may be surprised to find out after the concert that it was improvised. Some studies have even shown that there is no real difference between listening to a free improvised performance and a contemporary instrumental creation (Canonne 2019). There is no reason why this should not be the same in the case of electroacoustic improvisation.…”
Section: Analysing Electroacoustic Music Improvisationmentioning
confidence: 99%